Analysis of aerosol scattering properties and PM10 concentrations at a mountain site influenced by mineral dust transport. (15th September 2019) - Nicolás, J.F.; Castañer, R.; Galindo, N.; Yubero, E.; Crespo, J.; Clemente, A.
Abstract: Aerosol scattering properties (ASP) i.e., scattering and backscattering coefficients (σsp, σbsp, 525 nm), scattering Ångström exponent (SAE, 450–635 nm) and backscatter ratio (b, 525 nm) along with PM10 concentrations were measured from November 2015 to October 2016 at a mountain site (1558 m a.s.l) located in the southwestern Mediterranean. ASP and PM10 average values obtained for the whole period were: 26.2 Mm −1, 3.5 Mm −1, 1.42, 0.139 and 12.4 μg/m 3, respectively. The study was aimed at analyzing: a) the seasonal variability of the measured parameters, b) the impact of mineral dust from North Africa on PM10 and optical properties and c) the variation of ASP values and PM10 concentrations as a function of the mixing layer height. The extensive scattering properties had values ∼35% higher during the warm period, while SAE and b were similar during both the cold and warm seasons. σsp and σbsp increased under Saharan dust events (SDE). In contrast, SAE and b values showed a decrease due to the increase in coarse particle concentrations during this type of event. On non-event days, the lowest values of σsp and PM10 were recorded under free troposphere (FT) conditions (10.5 Mm −1, 3 μg/m 3 ). Conversely, SAE recorded its highest value (∼2.00) under these conditions, pointing to a predominance of fine particles in this layer. Average values of σsp and PM10 increased with the increase in the height of the Planetary Boundary Layer (PBL), while the SAE value progressively decreased to a steady value of 1.50–1.60. The average value of the mass scattering efficiency (MSE) during the study period was 1.35 m 2 /g. Highlights: The influence of Saharan dust and PBL height on scattering properties was analyzed. σsp and σbsp were different in the cold and warm periods, but SAE and b were not. σsp and PM10 increased under Saharan dust events, while b and SAE decreased. σsp and PM10 were lower under Free Troposphere conditions. The SAE mean value was lower than those found at other European mountain sites.